Public private partnership in the training of doctors after the 1990s' health sector reforms: the case of Tanzania - Nathanael Sirili; Gasto Frumence; Angwara Kiwara; Mughwira Mwangu; Isabel Goicolea; Anna-Karin Hurtig (BMC, 2019)
Abstract Similar to many other low- and middle-income countries, public private partnership (PPP) in the training of the health workforce has been emphasized since the launch of the 1990s' health sector reforms in Tanzania. PPP in training aims to contribute to addressing the critical shortage of health workforce in these countries. This study aimed to analyse the policy process and experienced outcomes of PPP for the training of doctors in Tanzania two decades after the 1990s' health sector reforms. We reviewed documents and interviewed key informants to collect data from training institutions and umbrella organizations that train and employ doctors in both the public and private sectors. We adopted a hybrid thematic approach to analyse the data while guided by the policy analysis framework by Gagnon and Labonté. PPP in training has contributed significantly to the increasing number of graduating doctors in Tanzania. In tandem, undermining of universities' autonomy and the massive enrolment of medical students unfavourably affect the quality of graduating doctors. Although PPP has proven successful in increasing the number of doctors graduating, unemployment of the graduates and lack of database to inform the training needs and capacity to absorb the graduates have left the country with a health workforce shortage and maldistribution at service delivery points, just as before the introduction of the PPP. This study recommends that Tanzania revisit its PPP approach to ensure the health workforce crisis is addressed in its totality. A comprehensive plan is needed to address issues of training within the framework of PPP by engaging all stakeholders in training and deployment starting from the planning of the number of medical students, and when and how they will be trained while taking into account the quality of the training.